Characterization of Spacesuit Associated Microbial Communities and Their Implications for NASA Missions - Danko, David; Malli Mohan, Ganesh Babu; Sierra, Maria A.; Rucker, Michelle; Singh, Nitin K.; Regberg, Aaron B.; Bell, Mary S.; O’Hara, Niamh B.; Ounit, Rachid; Mason, Christopher E.; Venkateswaran, Kasthuri (Frontiers in Microbiology, 2021)
Crewed National Aeronautics and Space Administration (NASA) missions to other solar system bodies are currently being planned. One high-profile scientific focus during such expeditions would be life detection, specifically the discovery of past or present microbial life, if they exist. However, both humans and associated objects typically carry a high microbial burden. Thus, it is essential to distinguish between microbes brought with the expedition and those present on the exploring planets. Modern spacesuits are unique, customized spacecraft which provide protection, mobility and life support to crew during spacewalks, yet they vent continuously, and the mobility of microbes through spacesuits has not been studied. To evaluate the microbial colonization of spacesuits, NASA used an Extravehicular Activity swab kit to examine viable microbial populations of 48 samples from spacesuits using both traditional microbiological methods and molecular sequencing methods. The cultivable microbial population ranged from below the detection limit to 9 x 102 colony forming units per 25 cm2 of sample and also significantly varied by the location. The cultivable microbial diversity was dominated by members of Bacillus, Arthrobacter, and Ascomycota. However, 16S rRNA-based viable bacterial burden ranged from 105 to 106 copies per 25 cm2 of sample. Shotgun metagenome sequencing revealed the presence of a diverse microbial population on the spacesuit surfaces, including Curtobacterium and Methylobacterium from across all sets of spacesuits in high abundance. Among bacterial species identified, higher abundance of Cutibacterium acnes, Methylobacterium oryzae, and M. phyllosphaerae reads were documented. The results of this study provide evidence that identical microbial strains may live on the wrist joint, inner gauntlet, and outer gauntlet of spacesuits. This raises the possibility, but does not confirm, that viable microbes are able to migrate between the interior and exterior of spacesuits. Overall, these data provide the first estimate of microbial dispersion from internal to external spacesuit surfaces, which will help future mission planners develop effective planetary protection strategies.